PENGELOLAAN KESAN SEORANG GAY DI KOTA PEKANBARU - Adhella Kasmita; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The phenomenon of homosexuality is a social phenomenon that can’t be denied the existence constituted as a reality in society and mixed reactions that vary in the surrounding environment. In general, people refer to homosexuals as a group of people who have an interest in feeling, both predominantly or exclusively to people of the same sex, with or without physical connections. Though admittedly or not, homosexuals have a social reality. This study aims to determine how a gay front stage and backstage in Pekanbaru.This research uses a qualitative descriptive research approach dramaturgy. The informants are a gay man in the city of Pekanbaru. Data collected by interview, observation and documentation. The data analysis technique based on the cycles Huberman and Miles in the form of data collection, data reduction, organizing data, and conclusions.The results showed that the informant's life as a society on the stage is the results of impression management are designed so that for the sake of the demands of life with life turned informant actually had a sexual deviant behavior. In the reality of life, to get a good assessment of other people about themselves while interacting, many preparations to be associated with the image itself, in terms of both physical and non-physical. Front Stage or the next stage is to see the full setting-an. It is an ideal concept that you want displayed by a person in accordance with the expectations of social communities through performances and existing styles. As